Feline gingivo stomatitis. Literature Review - Sousa Filho, Reginaldo Pereira de; Sampaio, Keytyanne de Oliveira; Azul Monteiro Evangelista, Janaina Serra; Cagnini, Didier Quevedo; Carvalho Mori da Cunha, Marina Gabriela Monteiro (Univ Federal Ceara, Centro Ciencias Agrarias, 2018)
Chronic gingivostomatitis is an oral pathology characterized by chronic inflammatory lesions mainly in the palatoglossal arch. The etiology is unknown but it seems that it's multifactorial with an immune-mediated component. The diagnosis should be based on history, clinical examination and laboratory tests, and therapy should be in performed according to each clinical case. This work aimed to make a brief review of the literature on the pathogenesis, clinical signs, diagnosis and treatment of feline chronic gingivostomatitis. Moreover, we intended to warn the veterinary clinicians about the importance of the disease and to discuss about the importance of the disease and present diagnostic and therapeutic difficulties according to the stage of the disease.
Keywords: Oral pathology; cats; FIV; sialorrhea